2012
DOI: 10.1016/s0140-6736(11)61878-3
|View full text |Cite
|
Sign up to set email alerts
|

Urbanisation and health in China

Abstract: China has seen the largest human migration in history, and the country's rapid urbanisation has important consequences for public health. A provincial analysis of its urbanisation trends shows shifting and accelerating rural-to-urban migration across the country and accompanying rapid increases in city size and population. The growing disease burden in urban areas attributable to nutrition and lifestyle choices is a major public health challenge, as are troubling disparities in health-care access, vaccination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
702
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,017 publications
(767 citation statements)
references
References 55 publications
20
702
3
3
Order By: Relevance
“…Some studies reported that immigrants have higher health risks because of lack of healthcare access, poor living and working environments, and a lack of social support (Gong et al, 2012;Hu et al, 2008aHu et al, , 2008b. Based on household survey data from Beijing in 2009, Chen (2011) suggested that the healthy-migrant phenomenon existed only for the physical health of rural-urban migrants but not for the mental health of the immigrants, which is worse than the local urban citizens.…”
Section: Health Migration and Settlementmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies reported that immigrants have higher health risks because of lack of healthcare access, poor living and working environments, and a lack of social support (Gong et al, 2012;Hu et al, 2008aHu et al, , 2008b. Based on household survey data from Beijing in 2009, Chen (2011) suggested that the healthy-migrant phenomenon existed only for the physical health of rural-urban migrants but not for the mental health of the immigrants, which is worse than the local urban citizens.…”
Section: Health Migration and Settlementmentioning
confidence: 99%
“…The right to access the urban public healthcare system is also a factor that cannot be ignored. Since rural-urban migrants are excluded from the urban public healthcare service system because of the hukou system (Gong et al, 2012), if rural-urban migrants are in poor health, they may be forced to go back to the countryside to seek alternative healthcare services. Second, earlier studies have shown that rural-urban migrants are at high risk of mental health (Cheung, 2014;Lin et al, 2011).…”
Section: Health Migration and Settlementmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse effect of long-term exposure to air pollution on type 2 diabetes risk is of much importance given the extraordinary confluence of high levels of air pollutants in urbanized environments, especially in rapidly urbanizing countries (23,25,26). Air pollution in China is a significant public health burden, especially in spring and winter (26,27). The pooled results of standardized risk estimates in the present meta-analysis suggest an obvious association of type 2 diabetes risk with long-term exposure to PM2.5 (Fig.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…The most significant impact of environmental change is public health. However, except for avian influenza, schistosomiasis and malaria [80][81][82][83] there are few studies involving remote sensing over China [84,85]. Atmospheric pollution cause health damages not only to urban residents but also to rural citizens [86].…”
Section: Perspectivesmentioning
confidence: 99%